2020
DOI: 10.1111/jph.12890
|View full text |Cite
|
Sign up to set email alerts
|

Curvularia asianensisandCurvularia eragrostidisassociated with leaf spot ofSansevieria trifasciatain Malaysia

Abstract: Leaf spot disease was detected on Sansevieria trifasciata in Malaysia. Two Curvularia species namely C. eragrostidis and C. asianensis were isolated as the pathogens. The isolated fungi were identified based on morphology and multigene phylogeny (ITS, GAPDH and TEF1‐α). Pathogenicity tests confirmed the roles of both Curvularia isolates in causing leaf spot of S. trifasciata. To our knowledge, this is the first report of C. eragrostidis and C. asianensis causing leaf spot of S. trifasciata in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Curvularia is reported to be a species-rich genus consisting of 131 species listed in Index Fungorum (assessed on 4 January 2018) 9 . The genus Curvularia acts predominantly as endophytes and pathogens of plants, animals, and humans 10 12 . Of note, Curvularia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Curvularia is reported to be a species-rich genus consisting of 131 species listed in Index Fungorum (assessed on 4 January 2018) 9 . The genus Curvularia acts predominantly as endophytes and pathogens of plants, animals, and humans 10 12 . Of note, Curvularia spp.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, C. lunata infection causes leaf spots on maize 19 and root rot on Strawberry 20 . Leaf spot on Sansevieria trifasciata 11 and postharvest rot on Pineapple 21 can be caused by C. eragrostidis, while C. hawaiiensis infection leads to leaf spot on rice 22 . In this study, the pathogenicity analysis revealed that diseased seedlings exhibited yellow, watery, and irregular lesions on their leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Certain species of Curvularia, such as C. asianensis and C. eragrostidis, can cause leaf spot disease in Sansevieria trifasciata, while C. lunata is responsible for sun ower leaf spot 10,11 . Effective management of the leaf spot disease in C. kwangsiensis requires identi cation of the pathogen and implementation of control measures.…”
Section: Introductionmentioning
confidence: 99%
“…(Kee et al 2019), Curvularia spp. (Kee et al 2020a), Fusarium spp. (Kee et al 2020b) as well as Colletotrichum neosansevieriae and Stachybotrys sansevieriicola (Crous et al 2015).…”
Section: Introductionmentioning
confidence: 99%